1996
DOI: 10.2527/1996.745934x
|View full text |Cite
|
Sign up to set email alerts
|

The growth performance, carcass characteristics, and meat quality of halothane carrier and negative pigs.

Abstract: Growth performance, carcass characteristics, and meat quality of halothane carrier (Nn) and negative (NN) pigs grown from 40 kg live weight and slaughtered at three weights (110, 125, and 140 kg live weight) were studied. Daily gains were similar for the two genotypes (974 g for Nn and 964 g for NN), but Nn pigs had a higher gain:feed ratio than NN pigs (P < .01). Dressing percentage was higher in Nn pigs than in NN pigs (P < .001), but there were no genotype differences for carcass length, backfat thickness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

47
99
10
23

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(182 citation statements)
references
References 23 publications
47
99
10
23
Order By: Relevance
“…It was the finding of Daza et al (2007) who studied the effect of the age at the beginning of the fattening period of Iberian pigs under free-range conditions. No influence of AM on pH measured at any time point was observed, in accordance with several authors who studied the effect of weight (Leach et al, 1996;Latorre et al, 2008a) or age (Weatherup et al, 1998;Latorre et al, 2009a) at slaughter on pH measured in the same muscle of heavy pigs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It was the finding of Daza et al (2007) who studied the effect of the age at the beginning of the fattening period of Iberian pigs under free-range conditions. No influence of AM on pH measured at any time point was observed, in accordance with several authors who studied the effect of weight (Leach et al, 1996;Latorre et al, 2008a) or age (Weatherup et al, 1998;Latorre et al, 2009a) at slaughter on pH measured in the same muscle of heavy pigs.…”
Section: Discussionsupporting
confidence: 91%
“…However, others have not found any effect (Leach et al, 1996;Unruh et al, 1996). The reason for these discrepancies is unknown, but either very high or very low water holding capacity, associated with dark, firm and dry (DFD) and pale, soft and exudative (PSE) problems have negative consequences on the quality of dry-cured meat products (Arnau et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was also found in some commercial crossbreeds with a significant effect of lower pH and a tendency to higher drip loss in females (Lloveras et al, 2008). It is generally accepted that the eating quality of pig meat (measured as tenderness, juiciness and flavour) is similar for castrates and females (Cisneros et al, 1996;Ellis et al, 1996;Leach et al, 1996). Storage effects.…”
Section: Genetic Variation In Meat Qualitymentioning
confidence: 62%
“…Keeping meat quality at an acceptable level during selection for leanness has been a problem in the pig breeding industry. For instance, numerous studies have reported the positive effect of the halothane genotype on carcass lean content and conformation; however, this positive effect was often accompanied by a negative effect on meat quality traits (De Smet et al, 1995 andLeach et al, 1996). Also in other studies aiming at increasing lean tissue growth by selection or by feeding strategies, a decrease in meat quality was noticed (Karlsson et al, 1993;Oksbjerg et al, 2000).…”
Section: Discussionmentioning
confidence: 99%